PLACENTAL GROWTH FACTOR (PIGF) DAN SOLUBLE FMS-LIKE TYROSINE KINASE-1 (sFIT-1) SEBAGAI PREDIKTOR KEJADIAN PRE EKLAMPSIA: MINI REVIEW (Politeknik Kesehatan Kemenkes Bandung, 2021)
Preeklampsi (PE) is an abnormality that occurs in pregnancy, which is characterized by an increase in blood pressure, appearance of urine protein and signs of organ damage that generally occurs above the gestational age of 20 weeks. The cause of PE is not yet known, but the problem thought to be related is the presence of placental malperfusion associated with abnormalities of maternal spiralist artery remodeling. The method of enforcing the diagnosis of PE that is still used today uses standard blood pressure enhancement, protein urine examination and other clinical conditions. Pregnant women are often diagnosed with PE have been accompanied by the condition of the IUGR fetus, or the mother with seizures because it has entered the eclampsia phase. These condition need another examination that can support the enforcement of PE diagnosis to predict the risk of PE in pregnancy, especially in at-risk groups. This mini review discusses the detection of PE using examination of blood vessel growth factors such as Placental Growth Factor (PIGF) dan soluble fms-like tyrosine kinase 1 (sFlt-1). Some research results show an increase in sFIT-1 levels and decrease in PIGF levels associated with PE conditions. sFlt-1 and PlGF ratios can be predictors for PE events.